Intracerebral Hemorrhage: Presentation, Early Morbidity and Mortality - Ullah, Qazi Ikram; Sherin, Akhtar; Khan, Adnan; Alam, Sardar M. (Journal of Postgraduate Medical Institute, 2011)
To study the mode of presentation, risk factors, early morbidity and mortality of patients presenting with intracerebral hemorrhage (ICH) to General Neurology unit. This study wa conducted at LRH, Peshawar from January to December 2001 on patients with confirmed ICH. Traumatic bleed was excluded from the study. After initial clinical assessment Glassgow coma scouring was done in all patients and the morbidity was assessed by modified ranking scale (MRS). Patient's MRS was recorded at the time of discharge and at one month follow up.Headache, vomiting and loss of consciousness are the common preseentations of ICH. short term outcome of ICH was satisfactory. GCS < 9 and hematoma size more than 60cm wer associated with higher mortality rate.